Underpinning beneficial maize response to application of minimally processed homogenates of red and brown seaweeds - Vaghela, Pradipkumar; Gandhi, Grishma; Trivedi, Khanjan; Anand, K. G. Vijay; Chavda, Dhruvil; Manna, Moutusi; Seth, Tanmaye; Seth, Abhiram; Shanmugam, Munisamy; Ghosh, Arup (Frontiers in Plant Science, 2023)
Sap from the fresh seaweed Kappaphycus alvarezii (KA) have been reported to improve crop growth, quality and stress alleviation. However, limited studies are reported for the minimally processed aqueous homogenates (MPHs) derived from dry seaweeds. The present investigation was envisaged to characterize the MPHs from the red seaweed KA and a brown seaweed Sargassum wightii (SW) and also assess the effect of foliar application on maize (Zea mays) crop performance when applied alone or in proportions ranging from 0-100%. Two doses (0.35 and 0.7%) were compared with control. Both the MPHs contained several compounds like retronecine, tyrosyl-glycine, hexyl 2-furoate, 1phosphatidyl-1D-myo-inositol, 12-(2,3-Dihydroxycyclopentyl)-2-dodecanone and trihomomethionine and many others which have known bioactivity for enhancing plant growth and providing stress tolerance. Both doses of Formatted: Font: Italic MPHs enhanced crop growth and yield, however, the best response was in general observed at lower dose. MPH of SW at 100% gave the highest seed yield at lower dose which was also at par with that obtained under lower dose of 100% KA. Other combinations, 80:20 and 40:60 KA:SW were also found to give comparable yields. The highest dose of 100% MPH of SW was found at par with control, a phenomenon that was investigated in detail with respect to metabolites and antioxidant profile in leaves as well as membrane modelling. Higher ROS, certain sugar and organic acids were observed in 100% MPH of SW at higher dose, although none of the antioxidant enzymes were significantly affected, nor was there any change in membrane characteristics of the leaf with respect to control as well as lower dose.Improvements in the seed yield were attributed to improved photosynthate production on account of higher dry matter accumulation in the MPH treated plants which may be also attributed to the presence of bioactive compounds in the biostimulants. In future, it is imperative to direct scientific investigations towards the quantification and identification of the most effective concentrations of these compounds within MPHs to optimize plant responses.The study connoted to beneficial use of the MPHs towards increasing crop production by employing optimum dose as foliar spray to crops.